Calculating Shock Wave Over pressure from High-Speed Video - Kelly Williams; Catherine Johnson (International Society of Explosives Engineers)
The ability to measure the overpressure of a shock wave is necessary for explosives research such as shockwave focusing and field testing of blast-resistant designs for buildings and vehicles. To record the peak overpressure of the nearly instantaneous pressure rise at the shock front, pressure transducers with a fast response rate and streamline pencil design are needed. Time spent setting up sensors coupled with the expense of high-frequency data acquisition systems, and the inconvenience of low impedance cables can make the process challenging. Additionally, only small inaccuracies in sensor position can drastically change the measurement recorded. Advances in high-speed video imaging make it possible to see the refraction of light due to the high-density gradient at the shock front without the need for parabolic mirrors or additional light sources necessary for Schlieren or shadowgraph imaging. The average shock front velocity between two points can be calculated by dividing the change in position by the elapsed time between the images. Using the Rankine-Hugoniot relationship demonstrated by Swisdak the peak overpressure of the shock wave can be calculated from its velocity eliminating the interference of the gage and mount. This paper investigates the accuracy of this method by setting dual transducer pencil probesat0and180 degrees perpendicular to the central axis of a285-gram(0.63-pound)cylindrical charge to record pressure versus time for comparison to the high-speed video. The axis of the camera lens is aligned with the central axis of the charge with both pencil probes in view. The pencil probes have two pressuretransducersset100millimeters (3.9 inches)apart to measure the time of arrival and are used to validate the velocities calculated from the high-speed images. This method can be used to evaluate the shock wave propagation from more complex prismatic charges with different cross-sectional shapes where precise placement of cumbersome pencil transducers in the near field is almost impossible.